Computer self-efficacy, learning performance, and the mediating role of learning engagement. - Chen, I-Shuo (Computers in Human Behavior, 2017)
This study examined the relationship between computer self-efficacy and learning performance and investigated learning engagement as a mediator of this relationship. The theoretical background is a combination of the conservation of resources (COR) theory and a theoretically extended job demands–resources model (JD-R model) proposed by Crawford, LePine, and Rich (2010). A daily diary design was carried out with 121 late-middle- and old-aged job seekers attending 10 computer cram schools. Participants completed a baseline questionnaire, seven daily diary questionnaires, and seven daily end-of-class computer skills examinations over the course of 1 week ( N = 121 ∗ 7 = 847 occasions). The results of multi-level analyses showed that 1) computer self-efficacy is positively related to learning performance, 2) computer self-efficacy is positively related to learning engagement, 3) learning engagement is positively related to learning performance, and 4) learning engagement fully mediates the relationship between computer self-efficacy and learning performance. The theoretical contributions, research limitations, implications for future research, and practical implications of this study are discussed.